Prevalence of depression among Science students during the COVID-19 pandemic period in Riyadh, Saudi Arabia - Abdulrahman Mahmoud, Mahmoud (Frontiers in Psychiatry, 2023)
The present study aimed to examine the prevalence of depression among science students during the COVID-19 pandemic. A survey-based study was conducted on 521 science students at Al Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia, using Beck’s Depression Inventory (BDI), during the course of the semester. Results showed that the Most students were female (62.19%). Sadness symptoms were observed among 59.69% of the students. We found a 77.74% overall prevalence of depression among students. Most individuals reported moderate BDI (25.34%), but extremely severe BDI was also reported in 7.29% of individuals. The BDI scores were highly significantly correlated with gender, education, and field of specialty (< 0.001) based on different statistical tests. BDI scores were significantly associated with number of the demographic and academic variables (p < 0.05). The study found significant symptoms of depression among students who displayed characteristics of depression during the COVID-19 pandemic. Therefore, students should undergo psychological counseling during difficult pandemic periods to prevent depression and mental stress.